Experiences from the first 10 years of a perinatal palliative care program: A retrospective chart review. Issue 1 (18th October 2019) - Doherty, Megan E; Power, Liam; Williams, Robin; Stoppels, Nahal; Grandmaison Dumond, Lynn
Abstract: Background: Perinatal palliative care is a relatively new component of paediatric palliative care which supports families who are expecting the birth of a child with a life-limiting condition. This study seeks to understand the characteristics of the infants and families referred for perinatal palliative care and the context for referrals in terms of diagnoses, referral characteristics, interventions, and outcomes. Methods: A retrospective chart review of infants with prenatally diagnosed life-limiting conditions that were referred for perinatal palliative care. Results: Eighty-five referrals were made for perinatal palliative care during the 10-year period, of which, 84 chose to continue with the service. Average gestational age at diagnosis was 23 weeks, and the mean time between diagnosis and referral to palliative care was 7 weeks. Stillbirths were common, occurring in 29% cases. Of livebirths, 59% of the infants survived for 2 days, and 80% died within 30 days. The most commonly referred conditions were trisomy 13 or 18 (24%), severe central nervous system malformations (20%), and severe congenital cardiac disease (16%). Referrals were most often made by neonatologists (39%), and maternal–fetal medicine specialists (36%). Discussion: Our study confirms previously observed characteristics of diagnosis, referrals, and outcomes, while providing the most detailed account of lifespans for particular diagnoses to date. Our findings validate the need for perinatal palliative care, as 99% of those referred continued with the service. Future research should adopt a prospective approach to identify critical factors affecting decision making of families and physicians in the wake of a life-limiting diagnosis.